(untitled) (Journal of Engineering, 2019)
This study “discusses the benefit of “addition waste paper as a “new cellulose material “in mortar mixes. A partial addition of waste paper by cement weight was achieved to produce cement composite mortar. Pulp and paper is the third major industrial dumper of air, soil and water. In recent year, paper and paperboard constitute a greater portion of many countries’ urban solid discarded generation. Beside, it increases characteristic “strength due to existence “of hydrogen links “in the microstructure of “paper. Furthermore, it consume “better thermal protection. The addition percentages “of waste paper used “in this work were (5%, 10%, 15% and 20%) by “mass of cement to measure and evaluate some “properties of the mortar produced (compressive“, direct “tensile, and flexural) strength, thermal “properties such as (thermal conductivity), and “microstructure investigation “like (scanning electron microscope “(SEM)). The results indicated that the fresh mortar “properties affected expressively with higher wastepaper percent. The mechanical properties (compression, direct tensile and flexural strength) were “reduced by increasing the content of waste paper, it reduces to (74%, 50%, and 86%) respectively, with (20%) addition of waste paper than the reference mix. Moreover, using waste “paper with different percentages “led to noticeable “decrease in thermal “conductivity, especially with increasing addition percentages.